О семантической эволюции фразеологических единиц - Синочкина, Б. М. (Kalbotyra, 1986)
The article is an attempt to analyse a number of Russian idioms as realization of the same phraseological model. The greatest attention is being paid to the Russian idiom ни шатко ни валко and its complicated semantic history.